MAELASviewer: An Online Tool to Visualize Magnetostriction - Nieves, Pablo; Arapan, Sergiu; Kądzielawa, Andrzej Piotr; Legut, Dominik (Sensors (Basel, Switzerland), 2020)
The design of new materials for technological applications is increasingly being assisted by online computational tools that facilitate the study of their properties. In this work, based on modern web application frameworks, the online app MAELASviewer has been developed to visualize and analyze magnetostriction via a user-friendly interactive graphical interface. The features and technical details of this new tool are described in detail. Among other applications, it could potentially be used for the design of magnetostrictive materials for sensors and actuators.
Keywords: visualization; magnetostriction; graphical user interface; web application; magnetoelastic effects